Z problematyki wynagrodzenia za udostępnianie utworu naukowego na podstawie art. 14 ust. 2 ustawy o prawie autorskim i prawach pokrewnych - Kozieł, Grzegorz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article presents selected problems concerning the remuneration for making a scientific work available by a scientific institution to third parties on the basis of Article 14 par. 2 of the Law of 4 February 1994 on Copyright and Related Rights (J.L. 2016, it. 666, as am. – CRRL), which is one of the powers of that institution provided for in that provision (other than the use of the so-called scientific material included in this work). The article deals with the issue of the legal nature of the provision of Article 14 par. 2 of the CRRL and the influence (impact) of the findings in this area on the scope of rights of the scientific work’s author in the field of remuneration. It also included an attempt to position of the right of scientific work’s author to remuneration of its being made available (in accordance with Article 14 par. 2 of the CRRL) in the extensive catalog of authors’ rights to remuneration provided for in this Law, including a proposal to determine the legal nature of the right to remuneration.